History of transformation of Chilean higher education (1973-1990) - Rifo Melo, Mauricio Esteban (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
This paper focuses on the institutional transformation of Chilean higher education carried out by the civic-military dictatorship between 1973 and 1990. The main contribution of this research lies in the search of the, so generically, called neoliberalism in higher education. From this emerges the historical interpretation according to which the transformation of Chilean higher education, during the civil-military dictatorship, was not marked by a trajectory of cumulative neoliberal change, but rather consisted of a field of dispute, together with a disruption with respect to what is understood as Neoliberalism in education. Therefore, the research is framed in studies on history of education. A historical and methodological strategy of hermeneutical approach guides the study and the use of information will be focused on the validation and testing of sources.